The impact of the malaria centre program on malaria incidence in Papua Province - Eni Setianingsih; Eny Sulistyaningrum (Public Health in Practice)
Objective: The goal of eliminating malaria in Indonesia by 2030 faces significant challenges, particularly due to the stagnation of malaria cases in recent years. This issue is exacerbated by the high concentration of cases in Eastern Indonesia, with Papua Province alone contributing to 86 % of the national malaria cases. To address this, the Malaria Centre Programme has been implemented to eradicate malaria in highly endemic regions. This study aims to evaluate the impact of the malaria centre program on the prevalence of malaria in Papua. Study design: a mixed-method approach. Method: First, fixed effects analysis effectively evaluates program impacts shaped by pre-existing attributes. Second, in-depth interviews help identify potential impacts, analyze mechanisms, and assess benefits to beneficiaries. Result: The findings indicate that the malaria centre program has successfully reduced the annual parasite incidence (API) in Papua Province by 31.81 cases per 1000 population. Additionally, controlling for healthcare facilities, especially the ratio of community health centres, significantly lowers malaria incidence by 430.695 cases. However, the availability of hospitals does not significantly impact malaria incidence in the province. Conclusion: The malaria centre program has had a significant impact on reducing malaria incidence in Papua Province. Implementing the program has effectively lowered malaria cases in several regencies, including Keerom, Nabire, Boven Digoel, and Jayapura.